Insights on the changing dynamics of cemetery use in the Neolithic and Chalcolithic of southern Portugal. Radiocarbon dating of lugar do Canto Cave (Santarém) - Faustino Carvalho, António; Cardoso, João Luís (SPAL - Revista de Prehistoria y Arqueología, 2015)
Lugar do Canto Cave is one of the most relevant Neolithic burial caves in Portugal given not only its extraordinary preservation conditions at the time of discovery but also the quality of the field record obtained during excavation. Its material culture immediately pointed to a Middle Neolithic cemetery but recent radiocarbon determinations also allowed the recognition of an apparent two step phasing of its use within the period (ca. 4000-3400 cal BC): an older one characterized by a single burial and a later reoccupation as a collective necropolis. Comparisons with other well-dated cave cemeteries in Southern Portugal permitted the recognition of changing funerary practices and strategies of cemetery use during the later stages of the Neolithic and the Chalcolithic: 1) ca. 3800 cal BC as the possible turning point from the practice of individual to collective burials; 2) alternating periods of intensive use and deliberate abandonment of cemeteries (evidenced by their intentional closure). Research avenues to investigate the social organization and ideological context underlying these aspects of the Neolithic communities in greater depth are tentatively pointed out in this paper.